2013
DOI: 10.1186/1752-1947-7-89
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracal cholecystitis calculosa in a right-sided posttraumatic diaphragmatic hernia: a case report

Abstract: IntroductionInjuries of the diaphragm were first described in 1541 by Sennertus and the initial repair was performed by Riolfi in 1886. Posttraumatic diaphragmatic hernia in adults is usually caused by blunt trauma and may remain asymptomatic and undiagnosed for many years. Right-sided tears are significantly less likely than left-sided tears because of the protective effect of the liver. They are associated with high mortality and morbidity. The rupture of the right side of the diaphragm and the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Prolapse of the gallbladder into the thoracic cavity in posttraumatic diaphragmatic hernia was reported in few articles [9][10][11][12][13]. An inflamed gall bladder (with stones) in the thoracic cavity was rare [14]. Malrotation of hepatic right lobe in our patient, which was confirmed by operation, may impair bile flow of microscopic bile duct and induce cholestasis, resulting in calculi formation in gallbladder for a long term.…”
Section: Case Reportmentioning
confidence: 65%
“…Prolapse of the gallbladder into the thoracic cavity in posttraumatic diaphragmatic hernia was reported in few articles [9][10][11][12][13]. An inflamed gall bladder (with stones) in the thoracic cavity was rare [14]. Malrotation of hepatic right lobe in our patient, which was confirmed by operation, may impair bile flow of microscopic bile duct and induce cholestasis, resulting in calculi formation in gallbladder for a long term.…”
Section: Case Reportmentioning
confidence: 65%
“…Tahiri et al [ 11 ] reported a case of a 57-year-old male presenting with respiratory symptoms leading to the diagnosis of prolapsed gallbladder and other abdominal organs through the right dome of the diaphragm. The patient had acute cholecystitis, and a cholecystectomy was done.…”
Section: Discussionmentioning
confidence: 99%
“…The injury is later diagnosed and corrected when it becomes clinically evident, usually due to complications of the contents of the hernia. However, the symptoms are uncharacteristic, making the diagnosis a challenge [2] . On the other hand, congenital diaphragmatic hernias are usually identified prenatally with ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%